Vomeronasal and Olfactory Structures in Bats Revealed by DiceCT Clarify Genetic Evidence of Function - Laurel R. Yohe; Simone Hoffmann; Abigail Curtis (Frontiers Media S.A., 2018)
The degree to which molecular and morphological loss of function occurs synchronously during the vestigialization of traits is not well understood. The mammalian vomeronasal system, a sense critical for mediating many social and reproductive behaviors, is highly conserved across mammals. New World Leaf-nosed bats (Phyllostomidae) are under strong selection to maintain a functional vomeronasal system such that most phyllostomids possess a distinct vomeronasal organ and an intact TRPC2, a gene encoding a protein primarily involved in vomeronasal sensory neuron signal transduction. Recent genetic evidence, however, shows that TRPC2 is a pseudogene in some Caribbean nectarivorous phyllostomids. The loss-of-function mutations suggest the sensory neural tissue of the vomeronasal organ is absent in these species despite strong selection on this gene in its mainland relatives, but the anatomy was unknown in most Caribbean nectarivorous phyllostomids until this study. We used diffusible iodine-based contrast-enhanced computed tomography (diceCT) to test whether the vomeronasal and main olfactory anatomy of several phyllostomid species matched genetic evidence of function, providing insight into whether loss of a structure is linked to pseudogenization of a molecular component of the system. The vomeronasal organ is indeed rudimentary or absent in species with a disrupted TRPC2 gene. Caribbean nectar-feeders also exhibit derived olfactory turbinal morphology and a large olfactory recess that differs from closely related bats that have an intact vomeronasal organ, which may hint that the main olfactory system may compensate for loss. We emphasize non-invasive diceCT is capable of detecting the vomeronasal organ, providing a feasible approach for quantifying mammalian chemosensory anatomy across species.